The chondroitin sulfate expression profile in human amniotic fluid cells: a time course study - Aungsuchawan, Sirinda; Keawdee, Junjira; Puaninta, Chaniporn; Pangjaidee, Nathaporn; Ong-Chai, Siriwan; Pothacharoen, Peraphan (Biomedical Sciences and Clinical Medicine, 2016)
Object The purpose of this study is to investigate the trend of expression of chondroitin sulfate epitope (WF6) in association with a continuous culture of hAFCs for a period of 30 days. Methods The hAFCs were obtained from the amniotic fl uid of pregnant women at 18 weeks of gestation (n=5). The cells were cultured in an RPMI 1,640 medium containing 20% FCS, Amnio-MAX-C100 16%, 0.03 mg/mL ampicillin and 0.1 mg/mL streptomycin (sigma, Buchs, Switzerland). The expression of chondroitin sulfate epitope (WF6) was detected continuously using immunocytochemistry and signal fl uorescence evaluated with the use of Image-pro Plus version 6.0. Results The levels of the mean area of the chondroitin sulfate WF6 was correlated with those of mean density. The fi rst cycle showed a gradual increase from day 0 to day 12 and then a continuous decrease from day 12 to day 18. In the second cycle the level increased from day 18 to day 27 and decreased after day 27 to day 30. Conclusion A reasonable conclusion is that the expression of chondroitin sulphate WF6 epitope in hAFCs gradually increased and then decreased in a cyclical pattern.